(5-Bromo-2-oxidoacetophenone 4-chlorobenzoylhydrazido)(triethylamine) nickel(II) - Ali, Hapipah Mohd; Yamin, B.M.; Khamis, N.A. (International Union of Crystallography, 2004)
In the title compound, [Ni(C15H12BrClN 2O2)(C6H15N)], the NiII atom exists in square-planar geometry, coordinated by a molecule of triethylamine through the N atom and by a tridentate Schiff base ligand via N and O atoms. No significant intermolecular interactions are found in the crystal structure. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.